Implementation of problem based learning model to improve students' understanding of reforestation and disaster mitigation - Mahulae, Parno Sumanro (Institute of Computer Science (IOCS), 2024)
This study aims to determine students' understanding of greening and disaster mitigation through the application of problem-based learning model. This research is a quantitative descriptive research. This research was conducted in grade 7 of SMP Negeri Poopo, Rayonapo District, South Minahasa Regency. The results showed that students' understanding of reforestation and disaster mitigation with respondents who became sample members as many as 42 students, as many as 11 students (26%) in the very good category, 20 students (48%) in the good category, 10 students (24%) in the good enough category, 1 student (2%) in the less good category. This means that with problem-based learning, students have a very good understanding of reforestation and disaster mitigation.